The Multi-Therapeutic Role of MSCs in Diabetic Nephropathy - Wang, Yi; Shan, Su-Kang; Guo, Bei; Li, Fuxingzi; Zheng, Ming-Hui; Lei, Li-Min; Xu, Qiu-Shuang; Ullah, Muhammad Hasnain Ehsan; Xu, Feng; Lin, Xiao; Yuan, Ling-Qing (Frontiers in Endocrinology, 2021)
Diabetic nephropathy (DN) is one of the most common diabetes mellitus (DM) microvascular complications, which always ends with end-stage renal disease (ESRD). Up to now, as the treatment of DN in clinic is still complicated, ESRD has become the main cause of death in diabetic patients. Mesenchymal stem cells (MSCs), with multi-differentiation potential and paracrine function, have attracted considerable attention in cell therapy recently. Increasing studies concerning the mechanisms and therapeutic effect of MSCs in DN emerged. This review summarizes several mechanisms of MSCs, especially MSCs derived exosomes in DN therapy, including hyperglycemia regulation, anti-inflammatory, anti-fibrosis, pro-angiogenesis, and renal function protection. We also emphasize the limitation of MSCs application in the clinic and the enhanced therapeutic role of pre-treated MSCs in the DN therapy. This review provides balanced and impartial views for MSC therapy as a promising strategy in diabetic kidney disease amelioration.